2022
DOI: 10.2147/dddt.s356988
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2-(5-Aryl-4,5-Dihydropyrazol-1-yl)thiazol-4-One as EGFR Inhibitors: Synthesis, Biological Assessment and Molecular Docking Insights

Abstract: Introduction Epidermal growth factor receptor (EGFR) regulates several cell functions which include cell growth, survival, multiplication, differentiation, and apoptosis. Currently, EGFR kinase inhibitors are of increasing interest as promising targeted antitumor therapeutic agents. Methods Different thiazolyl-pyrazoline derivatives ( 7a-o ) were synthesized and were first tested for anti-proliferative effect towards the A549 lung cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The docking results revealed that our target compounds demonstrated different types of bonds with these amino acids and illustrated the results of the biological evaluation. Looking at the literature, we find that erlotinib binds with the key amino acids in the binding site through H-bonding with Met769 and hydrophobic interactions with other amino acids, including the key amino acid Lys721 and Leu694 98 , 99 . Considering the docking studies, compounds 10c and 10d showed a binding affinity for the active site of EGFR comparable to that found for erlotinib.…”
Section: Resultsmentioning
confidence: 99%
“…The docking results revealed that our target compounds demonstrated different types of bonds with these amino acids and illustrated the results of the biological evaluation. Looking at the literature, we find that erlotinib binds with the key amino acids in the binding site through H-bonding with Met769 and hydrophobic interactions with other amino acids, including the key amino acid Lys721 and Leu694 98 , 99 . Considering the docking studies, compounds 10c and 10d showed a binding affinity for the active site of EGFR comparable to that found for erlotinib.…”
Section: Resultsmentioning
confidence: 99%
“…35 Overall, several studies have documented the selectivity of staurosporine against the T790M/L858R mutation of EGFR over wild-type EGFR ranging from 55 to ∼300 folds. 35−39 Moreover, staurosporine had also demonstrated dose-dependent inhibition of cell proliferation of A549 cells with IC 50 values ranging from 4.29 to 9.50 μM, 40,41 respectively. In addition, staurosporine also inhibits other lung cancer cell lines, such as N417, H209, and Ma-31, with IC 50 values of 54, 29, and 602 nM, 42 respectively, demonstrating its potency.…”
Section: ■ Methods Phytomolecule Identification and Experimental Datamentioning
confidence: 99%
“…For compound VI, it displayed antiproliferative activity for the breast cancer T-47D cell line with inhibition activity toward EGFR (IC 50 = 83 nM) [42] (Figure 1). According to the above data and in continuation of our scholarly interest in the chemistry of thiazolyl-pyrazolines and their biological activities [43][44][45], especially as possible anticancer agents [27,46,47], our objective was to enhance and modify a novel series of innovative thiazolyl-pyrazoline derivatives (4a-d, 5a-d, 6a, b, 7a-d, 8a, b, and 10a, b) as According to the above data and in continuation of our scholarly interest in the chemistry of thiazolyl-pyrazolines and their biological activities [43][44][45], especially as possible anticancer agents [27,46,47], our objective was to enhance and modify a novel series of innovative thiazolyl-pyrazoline derivatives (4a-d, 5a-d, 6a, b, 7a-d, 8a, b, and 10a, b) as potential dual-inhibitors against EGFR/HER2 with possible enhancement of their antiproliferative activities depending on introducing bioactive fragments like aryl-diazinyl, arylidene, isatin, or coumarin substitutions into the thiazole-pyrazoline combination as the core center (Figure 1). So, the basis and rationale of the design of target compounds as potential anticancer agents for breast cancer depend on the hybridization of the two bioactive scaffolds thiazole and pyrazoline which give greater anticancer activity by optimization of previous compounds by adding extra hydrophobic binding site and choosing the most active substituents (Cl and OCH 3 ) in the previous work [48] which depends on inhibiting MCF-7 which represent a very important candidate as they are used ubiquitously in research for estrogen receptor (ER)-positive breast cancer cell experiments and many sub-clones, which have been established, represent different classes of ER-positive tumors with varying nuclear receptor expression levels.…”
Section: Introductionmentioning
confidence: 92%